Recourse to the Apostolic Signatura: Article 123, §1, Pastor Bonus (Roman replies and CLSA advisory opinions 1997, 1997)
This text is taken from an information sheet prepared by the Apostolic Signatura to provide basic information to persons who make recourse to the Signatura or at least in dictate an interest in doing so. It is written for persons who do not have a technical knowledge of canon law and is not intended to be a complete treatment of this subject. Furthermore, it is written for person s who are of the Latin Church and thus does not cite the Code of Canons for the Eastern Churches.